Operator method in the problem of diffraction of waves on two graphene strips located in parallel planes - Калиберда, М.Е.; Погарский, С.А. (Radiotekhnika, 2017)
Diffraction of the - polarized plane electromagnetic wave in the THz range by two graphene strips placed in the parallel planes is considered. The operator method is used for the solution. The comparison of results with results obtained by the method of the hyper-singular integral equations for two graphene strips placed in the same plane is performed. The dependencies of the total scattering cross section, absorbance coefficient vs. frequency as well as near and far fields distribution at the plasmon resonance frequency are presented.